2011
DOI: 10.1080/07481187.2011.584758
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Presence Experiences and Meaning-Making in Bereavement: A Qualitative Analysis

Abstract: Acknowledgements:We would like to extend our sincere thanks to two anonymous reviewers and to Robert A. Neimeyer and Nigel Field for their invaluable and insightful advice and support in helping us to develop this article for publication.1 Address correspondence to Edith Steffen, Department of Psychology, University of Surrey, Guildford, Surrey, GU2 7XH, United Kingdom. E-mail: e.steffen@surrey.ac.uk, Tel.: +44 (0)1483 689553 Keywords: bereavement; continuing bonds; meaning-making; post-traumatic growth; sense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
63
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 47 publications
8
63
1
8
Order By: Relevance
“…During normal bereavement, the need to maintain attachment relationships increase and, for some, attachment-seeking efforts include communicating with ghosts or apparitions of the deceased (Kwilecki, 2011) or sensing the presence of the deceased during daily activities (Steffen & Coyle, 2011). Study findings have suggested that these supernatural experiences may compensate for anxious attachment experiences from early childhood.…”
Section: Unresolved Mourning Supernatural Belief Fantasy and Dissomentioning
confidence: 97%
See 1 more Smart Citation
“…During normal bereavement, the need to maintain attachment relationships increase and, for some, attachment-seeking efforts include communicating with ghosts or apparitions of the deceased (Kwilecki, 2011) or sensing the presence of the deceased during daily activities (Steffen & Coyle, 2011). Study findings have suggested that these supernatural experiences may compensate for anxious attachment experiences from early childhood.…”
Section: Unresolved Mourning Supernatural Belief Fantasy and Dissomentioning
confidence: 97%
“…These supernatural events may operate as imaginal attachment resources that support a sense of "earned security" and emotional regulation (Granqvist, Mikulincer, & Shaver, 2010). Optimally, spiritual or religious beliefs may offer greater meaning making (Frick, 2011;Steffen & Coyle, 2010;Steffen & Coyle, 2011) and a continuing bond with the deceased, whether externalized (hallucinations and illusions of the deceased) or internalized (mental representations of the deceased) (Field, 2006;Field, Gao, & Paderna, 2005).…”
Section: Unresolved Mourning Supernatural Belief Fantasy and Dissomentioning
confidence: 98%
“…For such purposes specifically, a variety of qualitative approaches have been espoused, such as phenomenology (Heath, 2000), discourse analysis (Wooffitt & Allistone, 2005), grounded theory (SimmondsMoore, Rhine-Feather, & Hamilton, 2008), thematic analysis (Steffen & Coyle, 2011) and the interpretive phenomenological approach (Roxburgh & Roe, 2013;Wilde & Murray, 2010). In the field of psychology more generally, Lyons (2009) reports a greater acceptance of qualitative methods of inquiry with regard to an increasing array of topics and research purposes.…”
mentioning
confidence: 99%
“…Through participant observation, the first author attempted to share the participants' naturalistic settings, foregrounding the participants' structuring of that world (Uzzell & Barnett, 2012). A social constructionist reading of interview data was also adopted 8 because, in Steffen and Coyle's (2011) qualitative study of sense of presence experiences, a focus on discursive aspects highlighted important dimensions within the data, such as the establishment of credible accounts and warding off alternative interpretations. This reading was 'discursive' in that it entailed the selective use of some analytic foci and techniques drawn from discourse analysis, thus locating itself within a social constructionist perspective.…”
Section: Analytic Proceduresmentioning
confidence: 99%
“…In a review of relevant literature (Steffen & Coyle, 2010), it was proposed that this experience could be conceptualized as a spiritual phenomenon. Building on this review, a recent qualitative study investigating the role this experience may play in meaning-making processes found that personal growth or finding meaning through the experience beyond immediate coping concerns required the availability of spiritual/religious frameworks which could be adopted or, if available but discrepant, could be accommodated to integrate the experience meaningfully (Steffen & Coyle, 2011).…”
mentioning
confidence: 99%